A murder of magpies - Flanders, Judith (Flanders, Judith. Sam Clair mysteries., 2015)
"It's just another day at the office for book editor Samantha Clair ... [including] lunch scheduled with gossipy author Kit Lowell, whose new book will deliciously dish the dirt on the fashion industry. But little does she know how much trouble Kit's book is about to cause-- before it even goes to print. When police inspector Field turns up at the venerable offices of Timmins & Ross, asking questions about an undelivered package that was addressed to Sam, she knows something is wrong. The messenger sent to deliver the package was murdered, and then Kit goes missing"--